Legal Protection and Gender Justice for Women in the Practice of Siri Polygamy: An Analysis of the Principles of Islamic Civil Law - Agnes Novita Br Simanjorang; Sri Hadiningrum; Parlaungan Gabriel Siahaan; Daniel Fransisto Hutabarat; Fahira Silva Dilla Nst; Theresia Mardiyana Tamba (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze Legal Protection and Gender Justice for Women in the Practice of Siri Polygamy: Analysis of the Principles of Islamic Civil Law. The practice of polygamy in Indonesia often causes injustice for women, who do not receive adequate legal protection. This study analyzes the relationship between the principles of Islamic civil law and the reality faced by women in the practice of siri polygamy. Although Islamic law emphasizes justice and protection of women's rights, many women are trapped in situations of injustice due to a lack of legal understanding and social stigma. This study uses a normative juridical method to explore the truth between legal norms and practices in the field. The results of the study indicate that minimal social support, lack of understanding of legal rights, and social stigma contribute to the injustice experienced by women. To improve legal protection and gender justice, it is recommended that there be recognition and registration of siri polygamous marriages, strengthening of legal regulations, assistance for women, and education and socialization regarding legal rights. With these steps, it is hoped that women's rights in the practice of siri polygamy can be fulfilled fairly within the framework of Islamic law and state law.